Stress phenotypes in epilepsy: impact on cognitive functioning and quality of life - Catalán-Aguilar, Judit; González-Bono, Esperanza; Lozano-García, Alejandro; Tormos-Pons, Paula; Hampel, Kevin G.; Villanueva, Vicente; Cano-López, Irene (Frontiers in Psychology, 2023)
Introduction Drug-resistant epilepsy has been proposed as a chronic stress model. Stress can be measured in terms of chronicity (epilepsy duration) and intensity (comorbidities), with depression and anxiety among the most important comorbidities in epilepsy due to its prevalence and its relationship with cognitive functioning and quality of life. This study aims to establish phenotypes according to how patients face a stressful condition (epilepsy) and examine differences in cognition and quality of life depending on these phenotypes. We hypothesize that there will be an interrelationship between epilepsy duration and negative affectivity, and these variables will influence cognition and quality of life. Methods 170 patients (82 men and 88 women) underwent a neuropsychological evaluation in which trait anxiety, depression, attention and executive function, verbal and visual memory, language, emotional recognition, and quality of life were assessed. Hierarchical clustering was performed using z-scores for three variables: trait anxiety; depression; and epilepsy duration. Results Three clusters were found: vulnerable (high negative affectivity and short duration); resilient (moderate negative affectivity and long duration); and low-impact group (low negative affectivity and short duration). Results show that the vulnerable group had poorer cognitive functioning and quality of life than the other groups. Specifically, the vulnerable group had poorer scores than the low-impact group on verbal memory, visual confrontation naming, and quality of life (except seizure worry). Furthermore, resilient patients had better scores than the low-impact group on cognitive flexibility variables, but lower scores on some quality-of-life subscales (i.e., overall quality of life, emotional well-being, and energy). Finally, the vulnerable group had poorer scores than the resilient group in executive functioning, naming, and quality of life. Discussion These results suggest that dealing with stress in patients with epilepsy is related to cognitive performance and quality of life. These findings underline the relevance of considering comorbidities in epilepsy and may be useful for detecting vulnerable or resilient profiles as risk or protective factors for cognitive and quality of life decline.